PERANCANGAN DAN PEMBUATAN GAME EDUKASI MENGGUNAKAN ADOBE ANIMATE PADA MATA PELAJARAN INFORMATIKA KELAS X DI SMAN 4 SUMBAR TAHUN AJARAN 2025/2026 - Anggina, Mifta Hunnisah; Wijaya, Indra; Yunus, Yuliawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the validity, practicality, and effectiveness of educational game-based learning media developed using Adobe Animate for the Informatics subject in Grade X at SMAN 4 SUMBAR. This study uses a research and development (R&D) method, using the ADDIE model which consists of 5 stages, namely Analysis, Design, Development, Implementation, and Evaliation. The subjects of the study were 35 students of class X.The result showed that the overall validity assessment conducted by experts on the educational game using Adobe Animate for class X at SMAN 4 SUMBAR was 95.97%, so the level of validity can be interpreted as very valid to use. The overall practicality test assessment of educational game using Adobe Animate for class X at SMAN 4 SUMBAR was 97.04%, so the level of practicality can be interpreted as very practical to use. The overall effectiveness test assessment of educational game using Adobe Animate for class X at SMAN 4 SUMBAR was 89.57%, so the level of effectiveness can be interpreted as very effective to use. The conclusion of this study is to produce an interesting and useful educational game learning media for teachers and students.